2015
DOI: 10.1007/s11356-015-4918-4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of sludge stabilization processes and sludge origin (urban or hospital) on the mobility of pharmaceutical compounds following sludge landspreading in laboratory soil-column experiments

Abstract: This study aimed to determine the effect of sludge stabilization treatments (liming and anaerobic digestion) on the mobility of different pharmaceutical compounds in soil amended by landspreading of treated sludge from different sources (urban and hospital). The sorption and desorption potential of the following pharmaceutical compounds: carbamazepine (CBZ), ciprofloxacin (CIP), sulfamethoxazole (SMX), salicylic acid (SAL), ibuprofen (IBU), paracetamol (PAR), diclofenac (DIC), ketoprofen (KTP), econazole (ECZ)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
8
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 56 publications
4
8
0
1
Order By: Relevance
“…SMX was the only PhC not detected. This result is consistent with other experiments at various scales, which have demonstrated its degradation by anaerobic digestion [ 9 ]. In spite of these results, the sorption behaviours of this compound and its main metabolite were evaluated.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…SMX was the only PhC not detected. This result is consistent with other experiments at various scales, which have demonstrated its degradation by anaerobic digestion [ 9 ]. In spite of these results, the sorption behaviours of this compound and its main metabolite were evaluated.…”
Section: Resultssupporting
confidence: 93%
“…Depending on these processes, sewage sludge can act both as a source or as a sink due to its adsorptive capacity [ 8 ]. The physicochemical properties of PhCs (log K ow , pK a ) and soil properties (organic matter, clay content and pH) can play a main role in the mobility of PhCs in soil and, consequently, in soil adsorption, leaching, plant up-take and/or interaction with terrestrial organisms [ 3 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…This hormone is usually quantified at concentrations lower than the ng/L range, which is not detectable with our analytical method (Backe 2015). Econazole is often mainly detected in the particulate phase (Lachassagne et al 2015), which was not analyzed in this work. Consequently, these two compounds are not included in the statistical analysis.…”
Section: Pharmaceutical Concentrationsmentioning
confidence: 90%
“…Ciprofloxacin was detected in both collections; however, collection A showed the highest concentration when compared with the other two drugs evaluated. According to Clarke and Smith (2011) and Yang et al (2017), ciprofloxacin is commonly found in sewage and SS, and for Lachassagne et al (2015), ciprofloxacin was the antibiotic that had the highest concentration in SS and the authors also confirm the high affinity of FQ for SS. In the study by Arun et al (2020), high levels of FQ were found, with ciprofloxacin being the most abundant and present in all samplings carried out in the study.…”
Section: Concentration Profile Of Drugsmentioning
confidence: 85%